In Contempt Defending Free Speech, Defeating HUAC - Yellin, Ed (University of Michigan Press, 2022)
"YOU ARE HEREBY COMMANDED to be and appear before the Committee on Un-American Activities of the House of Representatives of the United States, or a duly appointed subcommittee thereof, on February 10 (Monday), 1958, at ten o'clock a.m. at City Council Chambers, City Hall, Gary, Indiana, then and there to testify touching matters of inquiry committed to said committee, and not to depart without leave of said committee." So began a decade of hardship for Ed and Jean Yellin and their three young children as the repressive weight of the U.S. government, caught up in the throes of McCarthyism, crashed down upon their careers, their daily household budget, and their relationships to colleagues, neighbors, and their country. In Contempt is a faithful, factual testament to the enduring quality of patriotic dissent in our evolving democracy-and a loving reconstruction of what it meant to be labeled "unAmerican" for defending the Constitution.